An optimise drilling process for an aircraft composite structure using design of experiments - Mohd Ariffin, Mohd Khairol Anuar; Mohd Ali, M. I.; Salit, Mohd Sapuan; Ismail, Napsiah (Academic Journals, 2009)
The present work is focusing on an optimisation of the drilling cutting process for the composite sandwich panel. The study provided machinist with a simple procedure in order to minimise the damage events occurring during drilling process for composite material. A statistical approach is used to analyse the experiment data and it is called as design of experiment (DOE). The technique minimise the number of test required and maximizes the amount of reliable information. A glass fiber reinforced plastic (GFRP) sandwich part number of BMS 4 - 17 form boeing corporation is used for testing. There are 2 type of drill bit material were selected and 4 variable such as drill bit material, cutting velocity, feed rate and hole diameter. The results from this study shows that the minimum damage length is 0.05 mm and the maximum is 0.44 mm which are done at 3000 rpm, feed rate of 80.2 mm/rev for HSS and spindle speed at 500 rpm, feed rate of 246.8 mm/rev using carbide tool respectively.